Design and validation of an academic cyberloafing scale in university students - Pereyra Girardi, Carolina Iris; Mur, Julian Andres; Cirami, Lautaro (Revista Ecos de la Academia, 2025)
The accelerated adoption of technologies in education has driven academic interest in cyberloafing, exploring its impact on student behavior related to the use of the Internet during classes. This paper aims to design and validate an academic cyberloafing scale in Argentine university students. An exploratory factor analysis (EFA) was performed using polychoric correlations. The sample consisted of 310 university students from Argentina. Kaiser-Meyer-Olkin adequacy index = .780 and Bartlett’s test of sphericity x² =3428.9, p
Keywords: Argentina; Academic cyberloafing; University students; Psychometric validation